Math, asked by shreesanvith28, 4 months ago

solve the simultaneous equations 3x-5y=4 & 9x-2y=7
?only answer​

Answers

Answered by sunilsweety9177
3

Answer:

(i) We have, 3x−5y−4=0

⇒3x−5y=4...(i)

Again 9x=2y+7

⇒9x−2y=7...(ii)

By Elimination Method:

Multiplying equation (i) by 3, we get

9x−15y=12...(iii)

Subtracting (ii) from (iii), we get

9x−15y=12

9x−2y=7

−13y=5

⇒y=−

13

5

Putting the value of equation (ii), we get

9x−2(−

13

5

)=7

⇒9x+

13

10

=7

⇒9x=7−

13

10

⇒9x=

13

91−10

⇒9x=

13

81

⇒x=

13

9

Hence, the required solution is x=

13

9

,y=−

13

5

By Substitution Method:

Expressing x in terms of y from equation (i), we have

x=

3

4+5y

Substituting the value of x in equation (ii), we get

9×(

3

4+5y

)−2y=7

⇒3×(4+5y)−2y=7

⇒12+15y−2y=7

⇒13y=7−12

∴y=−

13

5

Putting the value of y in equation (i), we have

3x−5×(−

13

5

)=4

⇒3x+

13

25

=4

⇒3x=4−

13

25

⇒3x=

13

27

∴x=

13

9

Hence, the required solution is x=

13

9

, y=−

13

5

.

(ii) We have,

2

x

+

2

2y

=−1

6

3x+4y

=−1

∴3x+4y=−6...(i)

And x−

2

y

=3⇒

3

3x−y

=3

∴3x−y=9...(ii)

By Elimination Method:

Subtracting (ii) from (i), we get

5y=−15 ⇒y=−

5

15

=−3

Putting the value of y in equation (i), we get

3x+r×(−3)=−6

⇒3x−12=−6

⇒3x=−6+12⇒3x=6

Hence, Solution is x=2 , y=−3

By Substitution Method:

Expressing x in terms of y from equation (i), we have

x=

3

−6−4y

Substituting the value of x in equation (ii) from equation (i), we get

3×(

3

−6−4y

)−y=9

⇒−6−4y−y=9

⇒−6−5y=9

⇒−5y=9+6=15

∴y=

−5

15

=−3

Putting the value of y in equation (i), we get

3x+×(−3)=−6

⇒3x−12=−6

⇒3x=12−6=6

∴x=

3

6

=2

Hence, the required solution is x=2,y=−3

Answered by AryanAkshat72
1

Step-by-step explanation:

༆ ɑnswer ࿐

9 } Sol :— Given that

P (x) = 6x³ + 13x² + 3

g (x) = 3x + 2 = 0

:— 3x = 0 –2

3x = —2

x = —2/3

so, x = —2/3

put the value ...

p (—2/3) = 6 x (—2/3)³ + 13 x (—2/3)² + 3

= 6x —8/27 + 13 x 4/9 + 3

= —16/9 + 52/9 + 3/1

we will take LCM got = 9

= —16+52+27 / 9

= —16+79 / 9

= 63/8 Sol :— 7 Ans...

11 } Sol :— p(x) = 2x³+3x²—11x—3

g(x) = x + 1/2

:— x = —1/2

put the value ...

p(—1/2) = 2x (—1/2)³+ 3x (—1/2)²—11x (—1/2) —3

= 2x (—1/8) + 3x (1/4) —11x (—1/2) —3

= 2 x—1/8 + 3/4 — (—11) /2 —3

= —1/4 + 3/4 + 11/2 —3/1

we will take LCM got = 4

= —1 +3 +22 —12 / 4

= —1 +25 —12 / 4

= 24 — 12 / 4

= 12 / 4 Sol :— 3 Ans...

Hope it may help you...

༆ Mɑrk me ɑs brɑin list ɑnswer ࿐

Similar questions
Math, 11 months ago